Role of integrin α4 in the inhibition of fibrosis in activated hepatic stellate cells by Periplaneta americana extract - Fang, Ying; Liu, Ye; Li, Dingchun; Miu, Yi; Chen, Kexuan; Zhou, Jv; Xie, Lijuan; Chen, Xinting; Wu, Jingyan; Zhu, Ying; Lv, Lechun; Li, Wu (Frontiers in Pharmacology, 2025)
This study aims to investigate the role of integrin α4 (ITGA4) in the inhibition of hepatic stellate cells (HSCs) fibrosis by Periplaneta americana extract (PAE), as well as to explore its molecular mechanisms. In vitro experiments utilized TGFβ-induced LX2 and HSC-T6 cells to examine the anti-fibrotic effects of PAE, particularly through ITGA4 overexpression, to elucidate its involvement in PAE-mediated inhibition via the PI3K-AKT signaling pathway. Cell viability was assessed using the CCK-8 method, and the IC50 for PAE was determined through statistical analysis. We evaluated cell proliferation using scratch and EDU assays, and migration capabilities using Transwell assays. Molecular mechanisms were investigated through western blot (WB), quantitative PCR (QPCR), and transcriptome analysis. Results indicate that PAE reduces hepatic fibrosis by curbing hepatic stellate cells (HSCs) proliferation, migration, collagen synthesis, inflammatory cytokine production, and epithelial-mesenchymal transition (EMT). Additionally, while PAE suppressed ITGA4’s high expression in activated HSCs, ITGA4 overexpression counteracted PAE’s effects on HSC proliferation, migration, and collagen synthesis. These findings demonstrate that PAE primarily mitigates fibrosis in activated HSCs by inhibiting ITGA4, thus delivering anti-fibrotic effects in the liver.